'When my home is your business': Transforming stories of housing in a post-industrial city. Issue 2 (3rd July 2021) - Perry, J. Adam
Abstract: This article examines how performance-oriented arts practice with members of socially marginalised communities can be harnessed as a mode of grassroots civic participation, one that can transgress the expected norms of public communication that render some stories and speakers legitimate, and some not. The article will offer an analysis of a community-based theatre project that took place with a small group of high-rise tenants living in the mid-sized post-industrial city of Hamilton, Ontario, Canada. The project involved bringing together participants at risk of involuntary loss of housing due to increased gentrification. With a view to advancing a theoretical understanding of how adult educators can employ artistic practice to produce critical and public facing community-based pedagogies, the article engages with contemporary discussions related to the arts, public pedagogy and urban rejuvenation.